RANCANGAN SISTEM PELATIHAN BERBASIS KOMPETENSI BAGI KARYAWAN LEVEL MANAJERIAL - ARIEF ALFIANDRY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this research is the completion of a competency-based training system for managerial employees in the directorate Content Business MNC period 2008-2011. The object of research and the scope of the study is limited to developing a system of competency-based training for managerial-level employees in the directorate Content Business. Competency-based training system composed only covers aspects of the preparation of the training objectives, the selection of training methods, preparation of training materials, as well as the preparation of training evaluation. Competency-based training system composed only cover the system's core competency training, behavioral competency and role competency. The results obtained are the completion of a competency-based training system for managerial employees in the directorate Content Business MNC period 2008-2011 and its implementation plan. The key to successful implementation of the system of competency-based training as one of the implementation of the Human Resource Management (HRM) based on competency is communicating the purpose and benefits of the system implementation of competency based training to all ranks, starting from directors and gradually downward, so that the commitment and support is obtained from all sides. Implementation of competency-based training system as one of the implementation of the Human Resource Management (HRM) based on competency is a change that should also be considered ways to manage the changes that occur synergy.